Calibrated ages of Point Lena (PL) peat core from the USA - Eric S Klein; Robert K Booth (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.